Islam in Africa and the Middle East : studies on conversion and renewal - 483584 Levtzion, Nehemia; Abitbol, Michel; Nadan, Amos (Aldershot [England] ; Burlington, VT : Ashgate/Variorum)
Includes bibliographical references and index